2016
DOI: 10.2169/internalmedicine.55.7085
|View full text |Cite
|
Sign up to set email alerts
|

Major Increases between Pre- and Post-breakfast Glucose Levels May Predict Nocturnal Hypoglycemia in Type 2 Diabetes

Abstract: Objective The aim of this study was to determine whether nocturnal hypoglycemia may be predicted according to morning glucose levels. Methods We retrospectively evaluated 106 patients with type 2 diabetes who underwent continuous glucose monitoring during admission. The pre-breakfast glucose level (Pre-breakfast level), highest postprandial glucose level within 3 hours after breakfast (Highest level), time from the start of breakfast to the highest postprandial glucose level (Highest time), difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Mean differences between post-breakfast glucose spike, post-lunch glucose spike and post-dinner glucose spike and the IDF target (≤2.5 mmol/L) were also meta-analysed. The standard errors used in meta-analysis were calculated from standard deviations [6][7][8][9][10][11][12][13][14] and interquartile ranges [4] for each study [15][16][17]. The standard errors for the IDF target values were substituted with zero [18].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Mean differences between post-breakfast glucose spike, post-lunch glucose spike and post-dinner glucose spike and the IDF target (≤2.5 mmol/L) were also meta-analysed. The standard errors used in meta-analysis were calculated from standard deviations [6][7][8][9][10][11][12][13][14] and interquartile ranges [4] for each study [15][16][17]. The standard errors for the IDF target values were substituted with zero [18].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Twelve observational (eight cross-sectional, two longitudinal, one prospective and one retrospective) studies investigating fasting glucose, pre-meal glucose and postprandial glucose by CGM were included. Participants with known type 2 diabetes for 1.7 years [4] [10] were respectively used in eight studies. One study included newly diagnosed type 2 diabetes [8], and three studies did not report the sample's duration of diabetes [13,14,16].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Large clinical studies have shown that hypoglycemia and glycemic variability are associated with mortality in patients with diabetes mellitus [3][4][5]. We wanted to predict the Somogyi phenomenon, in which hypoglycemia and increased glycemic variability occur concomitantly, and we have previously reported that major increases between pre-and post-breakfast glucose levels may predict nocturnal hypoglycemia in type 2 diabetes [6].…”
mentioning
confidence: 99%